An ultra-sensitive suboptimal protospacer adjacent motif enhanced rolling circle amplification assay based on CRISPR/Cas12a for detection of miR-183 - Lu, Zhiquan; Wang, Shijing; Li, Ping; Yang, Huasheng; Han, Sanyang; Zhang, Shaochong; Ma, Lan (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction MicroRNAs (miRNAs) have been recognized as promising diagnostic biomarkers for Diabetic Retinopathy (DR) due to their notable upregulation in individuals with the condition. However, the development of highly sensitive miRNAs assays for the rapid diagnosis of DR in clinical settings remains a challenging task. Methods In this study, we introduce an enhanced CRISPR/Cas12a assay, leveraging suboptimal PAM (sPAM)-mediated Cas12a trans-cleavage in conjunction with rolling circle amplification (RCA). sPAM was found to perform better than canonical PAM (cPAM) in the detection of Cas12a-mediated ssDNA detection at low concentrations and was used instead of canonical PAM (cPAM) to mediate the detection. The parameters of reactions have also been optimized. Results and discussion In comparison with cPAM, sPAM has higher sensitivity in the detection of ssDNA at concentrations lower than 10 pM by Cas12a. By replacing cPAM with sPAM in the padlock template of RCA, ultra-high sensitivity for miR-183 detection is achieved, with a detection limit of 0.40 aM. within 25 min and a linear range spanning from 1 aM. to 1 pM. Our assay also exhibits exceptional specificity in detecting miR-183 from other miRNAs. Furthermore, the applicability of our assay for the sensitive detection of miR-183 in clinical serum samples is also validated. This study introduces a groundbreaking assay with excellent performance through a simple modification, which not only addresses existing diagnostic challenges, but also opens exciting new avenues for clinical diagnosis in the realm of DR.